2006
DOI: 10.1183/09031936.06.00005606
|View full text |Cite
|
Sign up to set email alerts
|

Soluble triggering receptor expressed on myeloid cells-1 in acute respiratory infections

Abstract: Levels of the soluble form of the triggering receptor expressed on myeloid cells (sTREM)-1 are elevated in severe sepsis. However, it is not known whether sTREM-1 measurements can distinguish milder bacterial infections from noninfectious inflammation. The present authors studied whether serum sTREM-1 levels differ in community-acquired pneumonia, exacerbations of chronic obstructive pulmonary disease (COPD), asthma and controls, and whether sTREM-1 may be used as a surrogate marker for the need for antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 33 publications
3
44
1
6
Order By: Relevance
“…[10][11][12] Among the critically ill patients analyzed in these studies, the determination of sTREM-1 proved to be a useful and highly sensitive parameter for accurate diagnosis. Further studies where sTREM-1 is detected in patients with chronic obstructive pulmonary disease, 13 peptic ulcer disease, 14 or inflammatory bowel disease 15 confirm the involvement of TREM-1 also in noncritically ill patient collectives and suggest that the activation of TREM-1 plays a general role in the innate inflammatory response. 7 However, a deeper understanding of how TREM-1 influences inflammatory responses and sepsis requires the characterization of the natural ligand for TREM-1 and its expression pattern.…”
Section: Introductionmentioning
confidence: 75%
“…[10][11][12] Among the critically ill patients analyzed in these studies, the determination of sTREM-1 proved to be a useful and highly sensitive parameter for accurate diagnosis. Further studies where sTREM-1 is detected in patients with chronic obstructive pulmonary disease, 13 peptic ulcer disease, 14 or inflammatory bowel disease 15 confirm the involvement of TREM-1 also in noncritically ill patient collectives and suggest that the activation of TREM-1 plays a general role in the innate inflammatory response. 7 However, a deeper understanding of how TREM-1 influences inflammatory responses and sepsis requires the characterization of the natural ligand for TREM-1 and its expression pattern.…”
Section: Introductionmentioning
confidence: 75%
“…The clinical significance of TREM-1 has been confirmed in several studies in which sTREM-1 is detected in patients with chronic obstructive pulmonary disease (20), peptic ulcer disease (21), or inflammatory bowel disease (22). The latter results underscore the involvement of TREM-1 also in noncritically ill patients and suggest that the receptor plays a general role in the innate inflammatory response (2).…”
mentioning
confidence: 74%
“…However, increasing amount of studies has shown that serum sTREM-1 is also significantly elevated in noninfectious inflammatory diseases (25)(26)(27). Phua et al observed a significant elevation of serum sTREM-1 levels in patients with COPD and asthma exacerbations compared with control objects, although this elevation was greater in patients with A. baumannii associated pneumonia (28). In the present study, an elevation of sTREM-1 levels in serum was observed after A. baumannii infection, trending similarly to the increase of bacterial colonies.…”
Section: Discussionmentioning
confidence: 99%